ANALYSIS OF DISTRICT MAINTENANCE ROAD ACCORDING TO THE ROAD MINIMUM SERVICE STANDARD (Case Study of the Jepara Regency Road Section in the District & Pecangaan Industrial Zone) - Eri Nugrahani; Moh Faiqun Niam (UNISSULA Semarang, 2019)
The convenience of road management has changed from the pattern of achieving the use of road stability models to achieving road Minimum Service Standards (MSS). In order to realize the minimum road service standards in Jepara, the regional government is still having difficulties in drafting the budget needed for road maintenance. The purpose of this research is to know the standard of road conditions, the condition of the existing district road and the strategy to realize the condition of district roads that are in accordance with Road MSS. Data analysis is done by calculating the standard of road conditions where the method of determining conditions uses IRI (International Roughness System) and RCI. Road conditions standarts according to the MSS Road are roads that have good and moderate conditions of 60% of the overall road segment in the region, with a standard assessment value of 0≤IRI≤ 8 or equivalent to 10≥RCI≥4.5. The condition of the good and moderate Pecangaan road - Damarjati is 2.7 km (87%), Bakalan-Pendosawalan-Pancur is 1.9 Km (32%), Damarjati - Gotri is 1.93 Km (35% ) roads in good and moderate conditions, and Lebuawu – Banyuputih is all good and moderate: 1.64 Km (100%). MSS Road conditions are only fulfilled in Lebuawu – Banyuputih (MSS 100%) and Pecangaan - Damarjati roads (87%). The handling strategy in order to reach MSS is prioritized on Bakalan - Pendosawalan - Pancur which requires a budget of Rp. 2,942,814,918, - and Damarjati - Gotri need a budget requirement of Rp. 2,228,207,878, -. Keywords: Road Maintenance; Minimum Service Standards; Road Conditions; IRI; RCI